Properties of fired clay bricks with incorporated biomasses: Cases of Olive Stone Flour and Wheat Straw residues. (15th January 2016) - Aouba, Laila; Bories, Cécile; Coutand, Marie; Perrin, Bernard; Lemercier, Hervé
Highlights: Modification of bulk density, porosity and thermal conductivity of fired clay bricks with organic matter. Technological impact of pore-forming agents on shrinkage, loss of ignition. Mechanical loss due to porosity created by fired organic matter. Abstract: In recent years, interest in green building materials and the valorisation of by-products from multiple industries has been increasing. As the brick industry allows various compounds to be added during the mixing procedure, much research has been conducted to highlight the impact of additions on fired clay bricks. This paper examines the significance of adding organic matter coming from agricultural solid waste (Olive Stone Flour, OSF, and Wheat Straw, WS residues) to improve thermal performance while maintaining load bearing capacity. The results show a decreasing bulk density for mixtures containing OSF, ranging from −6% to −19% compared to clay alone, and for WS mixtures, where the bulk density reduction is from −4% to −20%. Total porosity increases by 5–56% for OSF, and by 7–67% for WS, implying lower thermal conductivity for WS (−23% relative to clay alone) compared to OSF (−16%) when 5%.wt is incorporated. The compressive strength, for 5%.wt WS and 5%.wt OSF is −52% and −31% respectively. There is a significant positive correlation between the increasing amount of organic matter and the porosity. The most striking result to emerge from the data is that, for the same %.wt, WS creates higher total pore volume than OSF owing to the difference of grain size distribution. Consequently the pore size distribution of new materials containing OSF is more structured and leads to a better compressive strength than WS.